A health service for the nation (London : published by the Women Public Health Officers' Association)
1943-03-27 1943 1940s 8 pages 6. Several schemes have been formulated tor the provision of such medical treatment through a National Health Service, including that of the Planning Commission published by the British Medical Association, and that of the Socialist Medical Association. All these schemes suggest that the services of salaried general practitioners shall be available at "Health Centres" and, if necessary, in patients' homes, this new service superseding the present National Health Insurance and Poor Law general practitioner services ; these schemes also suggest that consultant and hospital services shall be at the disposal of the general practitioner. 7. The members of the Women Public Health Officers' Association attach very great importance to the retention and extension of existing environmental, preventive and educational health services. They believe that Health Visitors and other women Public Health Officers have contributed greatly to bringing about an improved standard of national health, and especially to the fall in the Infant Mortality rate from 150 to 50 per thousand in the last 50 years. 8. In the early years of this century, the greatest number of infant deaths was caused by "summer diarrhoea," due to feeding babies with contaminated raw milk. The spectacular reduction in the national Infant Mortality Rate has certainly been very largely due to the successful personal efforts of Health Visitors in teaching and convincing the mothers of the value of breast-feeding and of safe methods of bottle feeding. Such teaching is still necessary. 9. The remarkable diminution in cases of severe rickets is also largely attributable to the teaching and influence of Health Visitors, exercised both in the homes of the mothers and in the Welfare Centres. The weekly or fortnightly weighings at the Centres provide the opportunity for the Health Visitor to see the baby stripped and so to observe any early signs of rickets. Where these are present, the mother is referred immediately to the Centre Medical Officer, who gives detailed instructions with a view to preventing any further development of rickets. This advice will certainly deal with diet, clothing, sunshine and fresh air. It becomes the Health Visitor's duty to see that the mother realises the importance of carrying out this advice, and to help her to do so. This may well involve helping her, probably through the Housing Department of the local authority, to find and move into another house. The practice, even in narrow back streets, of leaving the baby nearly all day in its pram on the pavement is directly due to the teaching of Health Visitors. In former years the practice was to keep the baby in a dark corner near the fire. 10. As the scope of the medical services provided by local authorities has widened, each service has been popularised by the Health Visitors in the homes of the families concerned. Two 292/847/2/155